Improvement of carboplatin chemosensitivity in lung cancer cells by siRNA-mediated downregulation of DLGAP1-AS2 expression - Sania Ghobadi Alamdari; Reza Mohammadzadeh; Mohammad Amini; Souzan Najafi; Behzad Baradaran; Seyedeh Zahra Bahojb Mahdavi; Amirhossein Yari; Amir Ali Mokhtarzadeh (Scientific Reports)
Abstract Despite being one of the primary and most effective treatments for advanced stages of lung cancer, chemotherapy drugs like carboplatin have limitations due to their adverse side effects and the development of drug resistance in lung cancer cells. However, recent studies have shown promising results in using small interfering RNAs (siRNAs) as a therapeutic agent for cancer treatment. Hence, this study aimed to investigate the potential of combining siRNA-DLGAP1-AS2 with carboplatin in human lung cancer cell lines. The viability of the cells was assessed using the MTT assay, and apoptosis induction was examined through Annexin V/Pi staining. Additionally, the effect of the combination on cell cycle arrest and colony formation of lung cancer cells was studied. Furthermore, the expression of Bax, Bcl-2, MMP-2, MMP-9, GCLC, and CD44 was evaluated. Our functional analysis revealed that inhibiting the expression of DLGAP1-AS2 increased the sensitivity of lung cancer cells to carboplatin. Moreover, our study demonstrated that the combination of DLGAP1-AS2 inhibition through siRNA-DLGAP1-AS2 transfection and carboplatin treatment had a tumor-suppressive function, inhibiting the progression and proliferation of A549 lung cancer cells. Therefore, it can be concluded that targeting DLGAP1-AS2 using specific siRNA in combination with carboplatin chemotherapy holds promise as a valuable therapeutic approach for lung cancer.